Development of English Learning Media in Narrative Texts based on RPG Game with Pancasila Character at SMP Al-Ijtihad - Eka Uliyanti Putri Br Bangun; Fiqih Hana Saputri; Dimas Aji Syah Putra; Ridho Anwar (G-Tech: Jurnal Teknologi Terapan, 2024)
SMP Al-Ijtihad 2 Kuta Baru is a school located in Tangerang. Lack of learning media affects to the learning process. A variety learning media can increase student’s motivation towards learning English is an ongoing problem. So, Development of English Learning Media in Narrative Texts based on RPG Games with Pancasila Character was created to make it easier for students to learn English. The aim of this research is to develop an English educational game that can increase the interest and understanding of students regarding narrative text material containing the character of Pancasila in English subjects. The method used is the Waterfall Method. This research used Waterfall. The results of the development of learning media that is interesting, interactive and user friendly. From the results of calculating the level of feasibility, it can be seen that the satisfaction value of respondents from filling in the questionnaire is 95% of the 10 respondents. It can be concluded that the English learning media in narrative text with Pancasila characters has reached good impact and satisfactory level. In conclusion, the development of narrative text English learning media has good potential to increase students’ in SMP Al-Ijtihad 2 Kutbaru interest and understanding of narrative text material in English subjects.